Sistem Pendukung Keputusan Perangkingan Penjualan Produk Terlaris pada PT. Garuda Mitra Kimia Menggunakan Metode Aras Berbasis Android - Yogi Nanda Gunawan; Mutiara Sovina (Universitas Methodist Indonesia, 2026)
PT. Garuda Mitra Kimia is a company that distributes or sells chemicals and also distributes its products. Chemical inventory in the company is the most important thing for the company. The company must be ready to provide chemicals that are often needed by customers. A problem that often occurs at PT. Garuda Mitra Kimia is difficulty in determining the best-selling products so that product inventory is not structured according to the best-selling products. Often there are errors in inputting sales data so that the stock in the warehouse is not appropriate, which can complicate product inventory management so that sales reports for the best-selling products have not been properly systematized. To overcome these problems, PT. Garuda Mitra Kimia requires a system for product sales so that PT. Garuda Mitra Kimia can determine product inventory stock for best-selling products. The result of this study is an Android-based system by implementing a decision support system to determine the sales of best-selling products at PT. Garuda Mitra Kimia using the ARAS method, which aims to make it easier for companies to obtain sales reports for best-selling products with appropriate and well-systematized management data.